Native AMF Communities in an Italian Vineyard at Two Different Phenological Stages of Vitis vinifera - Cesaro, Patrizia; Massa, Nadia; Bona, Elisa; Novello, Giorgia; Todeschini, Valeria; Boatti, Lara; Mignone, Flavio; Gamalero, Elisa; Berta, Graziella; Lingua, Guido (Frontiers in Microbiology, 2021)
Arbuscular mycorrhizal fungi (AMF) are beneficial soil microorganisms that can establish symbiotic associations with Vitis vinifera roots, resulting in positive effects on grapevine performance, both in terms of water use efficiency, nutrient uptake and replant success. Grapevine is an important perennial crop cultivated worldwide, especially in Mediterranean countries. In Italy, Piedmont is one of the regions with a longest winemaking tradition. In the present study, we characterized the AMF communities of the soil associated or not with the roots of V. vinifera cv. Pinot Noir cultivated in a vineyard subjected to conventional management using 454 Roche sequencing technology. Samplings were performed at two plant phenological stages (flowering and early fruit development). AMF community was dominated by members of the family Glomeraceae with a prevalence of the genus Glomus, and the species Rhizophagus intraradices and R. irregularis. On the contrary, the genus Archaeospora was the only belonging to the family Archaeosporaceae. Since different AMF communities occurs in the two considered soils, independently from the plant phenological stage, a probable role of V. vinifera in determining the AMF populations associated to its roots has been highlighted.